2015
DOI: 10.1002/tesj.213
|View full text |Cite
|
Sign up to set email alerts
|

Moving BeyondYes or No: Shifting From Over-Scaffolding to Contingent Scaffolding in Literacy Instruction With Emergent Bilingual Students

Abstract: Building on theories of scaffolding and previous research on scaffolding between adults and children, this article provides empirical examples of over-scaffolding as it occurs in peer-topeer literacy activities among elementary-level emergent bilingual students. In their analysis of data from the first year of a design-based research project (Bradley & Reinking, 2011) consisting of a cross-aged peer-tutoring program, the authors shed light on how their curriculum tools unintentionally overscaffolded students' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 50 publications
2
37
2
Order By: Relevance
“…EL teachers can also honor student aspirations in their instructional practice, by thinking carefully about curricular articulation and avoiding over-scaffolding (Daniel, Martin-Beltrán, Peercy, & Silverman, 2016). Research finds that EL content courses tend to be much less rigorous than their mainstream counterparts, and that a sustained lack of rigor has a harmful effect on students (e.g., Callahan, 2005;Olsen, 2014).…”
Section: S P E C I a L I S S U Ementioning
confidence: 99%
“…EL teachers can also honor student aspirations in their instructional practice, by thinking carefully about curricular articulation and avoiding over-scaffolding (Daniel, Martin-Beltrán, Peercy, & Silverman, 2016). Research finds that EL content courses tend to be much less rigorous than their mainstream counterparts, and that a sustained lack of rigor has a harmful effect on students (e.g., Callahan, 2005;Olsen, 2014).…”
Section: S P E C I a L I S S U Ementioning
confidence: 99%
“…Third, because contexts and tools shape comprehension, a critical perspective can show how planned scaffolds could lead to overscaffolding, wherein teachers assume that the learners need more extensive support than they really do, unintentionally limiting learners’ opportunities to make sense of texts (Mertzman, ). For example, Daniel, Martin‐Beltrán, Peercy, and Silverman's () work on a larger design‐based research project studying a cross‐age peer tutoring program showed how a team of teachers and researchers closely analyzed student discourse during comprehension instruction, finding that their carefully planned curriculum had inadvertently steered students into limited comprehension discussions. Then, the team subsequently revised the curriculum to decrease the amount of planned scaffolding and afford more flexible opportunities for contingent scaffolding, and ensuing iterations saw students’ discussions demonstrate much richer comprehension.…”
Section: The Need To Focus On Contingencymentioning
confidence: 99%
“…Third, these findings emphasize that the joint enterprises valued in a community can shape how LOTEs are used to undertake these enterprises. Findings underscore the importance of structuring activities that align with constructivist approaches to instruction (Daniel, Martin‐Beltrán, Peercy, & Silverman, ; Windschitl, ). In Ms. Ash's classroom, students had few opportunities to use language in extended discourse, which could then serve as a shared resource for future meaning making.…”
Section: Discussion: Making Meaning With Lotes Across Classroomsmentioning
confidence: 90%